Implementation of solar panels and photovoltaic systems as an alternative for efficient energy saving at Universidad Nacional Abierta y a Distancia-UNAD - Gómez, Edna Vanessa Ramos; Vargas, Carlos Eduardo Bohórquez; Devia, Karen Lorena Arias; Gutierrez, Daniela Carolina Herrera (Universitas Diponegoro, 2022)
The Universidad Nacional Abierta y a Distancia- UNAD, is a public, educational organization of the National Order that through the conception and practice of Distance Education was not affected in the development of activities in the time of pandemic, according to its solid technological infrastructure to promote the virtuality.One of the principal changes implied by the preventive isolation because of COVID-19 was to reassess the context of the management system and the expectations and demands of the stakeholders, generating new opportunities and risks as a result of the sanitary situation. This situation, strengthening the commitment of the Environmental Management System with climate change based on the sustainable development objectives and the 2019-2023 internal development plan, which refers within its main goals, to the installation of 8 solar tables and 2 photovoltaic systems for outdoor lighting in different locations, in addition to operational control activities that contribute to mitigating the impacts of the activities associated with the work at home and on-site modality, giving environmental legal compliance and expanding the scope to ISO 14001:2015 certification in new centers, thus promoting new challenges that have allowed the positioning in good environmental practices of the University at the national level. Keyword: Sustainable Development Goals, Energy, photovoltaic lighting systems, carbon footprint